At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
Combines polynomials with systems of linear equations. Like I told Faye, the way to get the remainder when f(x) is divided by (x-c) is to simply plug in c into the function. IE Remainder of p(x) when it's divided by x-1... is just p(1) So... what is p(1)
mhmm so p(1) = ?
i was just asking what x-c is.
Just an example.
Or, a formula. In this case, x-c is x-1
So, c=1 now just plug in 1 into the function p(x) = x² + ax - b
Simplify -.- 1² + a(1) - b = 1 + a - b Okay, and this is equal to -6, as per the given. -6 = a - b + 1
sorry,, typo,, its not -6 its only 6
hmm... 6 = a - b + 1 Understood?
Or, simplify further, we get a - b = 5
... stay with me here...
why 6 = a - b + 1??? where did you get +1??
Focus... since the remainder of p(x) when it's divided by x-1 is 6, it can only mean that p(1) = 6 p(1) = 1² + a(1) - b = 1 + a - b etc
ahah, xDD sorry,, didn't see thatxDD
You know a-b = 5 That's not enough to know the value of a and b, you need another equation. Now that we mention it... we have another fact... that when it's divided by x + 2, the remainder is 3. Can only mean that p(-2) = 3 Solve this part.
Hey... p(-2)... what is it?
sorry,, we just started doing that today, xDD
No better time than now. It's just plugging in x = -2... how hard can it be? :P p(-2) = ?
And this is equal to...?
my eyes hurts,.. T_T
-.- my eyes *hurt* and anyway... you're losing focus...
Don't you just hate it when the other kid gets the right answer and then 'corrects' it with an incorrect one -.-
Okay, no more guessing... show your work :P
Show your work... let me know you're not guessing...
(-2)^2+a(-2)-b=3 4-2a-b=3 -2a-b=3-4 -2a-b=-1 -2a-b=-1 divide by -1 2a+b=1
Much better. Now you have both a - b = 5 and 2a + b = 1 I can trust you can solve this system with ease now?
We certainly have a lot to work on -.- FIRST EQUATION a - b = 5 adding b to both sides gives a = b + 5 Now substitute b+5 for the a in the SECOND equation: 2(b+5) + b = 1 SOLVE FOR b. Get to it...
a=2 b=-3, correct ba toh??
Nice going, *peanut-butter boy* :P
da eff???? how da eff,,
pff... Google Derek Bocar... first result... You take so long, I have to find ways to ... kill time... and guess what came up? XD
yeah,, that was really long time agoo, T_T
most humiliating scandal
mhmm... last bit just killed my appetite :D
But enough about that. Job well done... you certainly picked this up with more speed than Faye...
i'm really sleeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeepyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyy!!!!!!
Join the club. Why don't you listen to yourself playing? >:)
LOL Just kidding Peace ^_^
i'm gonna hack their youtube account!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!1
Come to think of it... just how good are you with that fiddle?
ahm,, xDDD average?? xDDD not really an expert,
figures... that's no use, I need to hear it. Any excerpts?
i don't really play classical music, so long,,,, xDDD
nope,, i don't really show my skills too much, xDD
Le gasp... okay, interest over XD time to play some notes on a keyboard... ...the one that looks like a monster's smile and not the one with QWERTY written on it...
@derek11111 Listening to myself play is making me even sleepier... you should follow suit. Good night, -peanut butter boy- XD -------------------------------------- Terence out ^_^